The BecA Hub at ILRI — A new research facility in Africa and for Africa - International Livestock Research Institute (International Livestock Research Institute, 2010)
The Biosciences eastern and central Africa Hub, hosted and managed by the International Livestock Research Institute, in Nairobi, Kenya, works on Africa’s most important agricultural problems. This new facility is the only one of its kind on the continent. Through the voices of students, this film explores the expertise, laboratories, services and training that this new state-of-the-art research platform provides to research students and scientists in Africa and beyond.